Increasing the Capacity of Teacher and Parents of Kindergarten Sanimah Through Training to Make Functional Objects of Flower Pot Hangers - La Diadhan Hukama; Zainal Zawir Simon; Verni Y. Ismail; Zulihar Zulihar; Efendy Zain (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2019)
This community service activity aims to increase the insight and knowledge of Do It Yourself by providing training in making functional objects, pot hangers made of rope and cloth ropes for teachers, parents of Islamic Sanimah Kindergarten students and PKK cadres RW 11 Cempaka Putih Barat, Central Jakarta. The method of community service activities uses the lecture method, demonstration, question and answer method as well as training in the manufacture of functional objects flower pot hangers. The result of this community service activity was training on making functional flower pot hangers. About 90% of the training participants were able to make macrame crafts in the form of pot hangers made of rope and cloth ropes.